Syntheses and Antimicrobial Activities of Derivatives of 3-Amino-2-methyl-quinazolin-4-(3H)-one - Chhabra, G.S.; Tiwari, Ravi (Asian Journal of Chemistry, 2010)
In the present study, 3-amino-2-methyl-quinazolin-4-(3H)-one (1) have been synthesized by the reaction of N-acetyl anthranilic acid with acetic anhydride followed by treating the mixture with hydrazine hydrate in pyridine. Compound 1 on treating with chloro acetyl chloride gives 3-chloroethanoylamino-2-methyl-quinazolin-4-(3H)-one (2). The final compounds 4a-g were obtained by reacting the substituted derivative 2 with aliphatic and aromatic secondary amines. The structural assignment of this compound 4a-g has been made on the basis of elemental analysis, IR and 1H NMR data. The synthesized compounds were screened for in vitro growth inhibiting activity by determining the minimum inhibitory concentration against different strains of bacteria and fungi. Compounds 4a, 4b, 4e and 4g exhibit highest antibacterial activity and compounds 4a, 4b, 4d and 4e showed better antifungal activity.